Pak1, adjuvant tamoxifen therapy, and breast cancer recurrence risk in a Danish population-based study. (2nd June 2016) - Ahern, Thomas P.; Cronin-Fenton, Deirdre P.; Lash, Timothy L.; Sørensen, Henrik Toft; Ording, Anne Gulbech; Hamilton-Dutoit, Stephen J.; Hellberg, Ylva
Abstract: Background Adjuvant tamoxifen therapy approximately halves the risk of estrogen receptor-positive (ER+) breast cancer recurrence, but many women do not respond to therapy. Observational studies nested in clinical trial populations suggest that overexpression or nuclear localization of p21-activated kinase 1 (Pak1) in primary tumors predicts tamoxifen failure. Material and methods We measured the association between Pak1 expression and breast cancer recurrence in a Danish population-based case-control study. Pak1 cytoplasmic expression level and nuclear positivity were determined by immunohistochemical staining of primary breast tumors from recurrence cases and matched controls from two breast cancer populations; women diagnosed with ER-positive tumors who received at least one year of tamoxifen therapy (ER+/TAM+), and women diagnosed with ER-negative tumors who survived for at least one year (ER−/TAM−). Pak1 staining was assessed by a single, blinded pathologist, and associations were estimated with conditional logistic regression models. Results We included 541 recurrence cases and 1:1 matched controls from the ER+/TAM + group and 300 recurrence cases and 1:1 matched controls from the ER−/TAM − group. Pak1 cytoplasmic intensity was not associated with breast cancer recurrence in either group (ER+/TAM + ORadj for strong vs. no cytoplasmic staining = 0.91, 95% CI 0.57, 1.5; ER−/TAM − ORadj for strong vs. no cytoplasmic staining = 0.74, 95% CI 0.39, 1.4). Associations between Pak1 nuclear positivity and breast cancer recurrence were similarly near null in both groups. Conclusion Pak1 positivity in primary breast tumors was neither predictive nor prognostic in this prospective, population-based study.